Preliminary revision of Alpheus djeddensis Coutière, 1897 species complex, with description of three new species of goby-associated snapping shrimps and taxonomic notes on A. macellarius Chace, 1988 and A. djiboutensis De Man, 1909 (Decapoda: Alpheidae) - Anker, Arthur (Zootaxa, 2024)
The present study deals with several species of goby-associated snapping shrimp in the taxonomically challenging Alpheus brevirostris (Olivier, 1811) species group. Alpheus djeddensis Coutière, 1897 is redescribed based on two specimens from the original type series and material recently collected on the Red Sea coast of Saudi Arabia. Alpheus djiboutensis De Man, 1909, a species without extant type material, is removed from the synonymy of A. djeddensis after a careful analysis of the original description by De Man (1909). A cryptic species, morphologically undistinguishable from A. djeddensis, but with a significant divergence in the COI gene sequence and several consistent differences in colour pattern, is described as A. shukran sp. nov., based on material from Oman and Saudi Arabia. Both A. djeddensis and A. shukran sp. nov. are closely related to A. macellarius Chace, 1988, another potential species complex. Two species previously confused with A. djeddensis or A. djiboutensis in ecological literature and underwater field guides are described as A. tigrinus sp. nov. and A. berumeni sp. nov., based on material from the Red Sea, mainly Saudi Arabia. Each of them has a unique and diagnostic colour pattern and differs from A. djeddensis and A. djiboutensis by a few subtle morphological characters. The identity of the material preliminarily identified as A. cf. tigrinus and A. cf. berumeni from localities outside of the Red Sea needs to be confirmed by molecular analyses. Finally, three specimens from the Red Sea coast of Saudi Arabia are preliminarily identified as A. cf. djiboutensis; their true taxonomic identity, however, remains to be clarified further. All available information on goby associations for the herein treated species is provided.